Adaptive Varifocal Lenses Based on Dielectric Elastomer Actuator - Shibiao Li; Lin Liu; Haoyue Xing; Zhaohui Li; Yang Cheng (Photonics)
Optical imaging systems using varifocal lenses have been widely used in many applications over the past several decades, such as machine vision devices, consumer electronic products, and medical instruments. Traditional varifocal lenses often consist of multiple solid focal length refractive optical elements. The varifocal ability is obtained by dislocating these optical elements along the optical axis over specific distances using mechanical driving mechanisms. It makes the traditional optical varifocal imaging systems suffer from bulky dimensions, slow response speed, complicated configuration, and discrete magnifications. Adaptive varifocal lenses have been a better choice to address the aforementioned limitations of traditional varifocal lenses. Dielectric elastomer actuators (DEA), which can effectively respond to an electric field and result in shape deformation, have been used to develop various adaptive lenses. This paper aims to give a brief review of adaptive varifocal lenses based on DEA. First, this paper describes the basic physical mechanism of DEA. Second, this paper reviews adaptive varifocal liquid lenses based on DEA and introduces their material, structure, and fabrication process, focusing on their unique advantages, such as fast response speed and compactness. However, despite these merits, the adaptive varifocal liquid lens still has challenges in environment stability and liquid leakage. To address these challenges, adaptive varifocal soft solid lenses based on DEA have been proposed, which are also reviewed. In addition, other adaptive varifocal lenses, including metalens, Fresnel lens, microlens array, and Alvarez lens, are also presented. Finally, the prospects and challenges for the development of adaptive varifocal lenses based on DEA are discussed.